Clinical, Laboratory, and Perioperative Management Characteristics in Liver Resection Cases in Fatmawati General Hospital - Darnindro, Nikko; Marsigit, Jessica; Nugroho, Adianto; Sari, Anggraini Permata; Taufik, M Azhari; Adrisyel, Dieby; wardoyo, Elizabeth Yasmine; Ratnaningrum, Apriliana; Darmawan, Danny (The Indonesian Society for Digestive Endoscopy, 2022)
Background: Liver resection has been associated with high morbidity and mortality. Improvements in surgical, anesthetic techniques, and multidisciplinary collaborations, can reduce post-surgery complications and mortality. This study aims to provide an overview of the perioperative conditions and the treatments after liver resection.Method: A retrospective study of liver resection surgery between 2019-2020 at Fatmawati Hospital.Results: Of the 11 patients, mean age was 49.7 years, with 63.6% being female and mean BMI was 22 kg/m2, hypertension and diabetes mellitus were found in 18.2% and 18.2% of patients respectively. HBsAg reactive was detected in 36.3%. Based on pathology, HCC was found in 54.5%, while 18.2% were metastatic adenocarcinoma. Postoperative hyperglycemia was observed in 90.9%. Increase in AST and ALT 3 upper limit normal were found in 90% and 72.7% of patients. Mean AST and ALT were 408.3 U/L and 246.18 U/L. Mean urine production at 8-, 16-, 24-, and 48-hours post-operative were 757, 1624, 1880 and 1930 cc. Urine production ≤ 500 cc in the first 8 hours was detected in 44.4% of patients, and elevated creatinine levels 50% post-operative occurred at 11.1%, 22.2%, 22.2% at 16, 24, and 48 hours post-op. Renal support therapy was given to 5 of the 11 patients. D-Dimer levels were increased in all patients.Conclusion: Adequate fluid monitoring and metabolic disorders control such as glucose levels, acute kidney injury, coagulation disorders, and bleeding are important things that need to be considered in the perioperative management of liver resection.